Rehabilitation with ceramic veneers: Knowing the clinical practice of dentist (Research, Society and Development, 2023)
Objective: to know the clinical practice of dentists who work with rehabilitations with ceramic laminates. Method: this is a qualitative and quantitative study carried out from March to April 2023. Dental surgeons with clinical practice in rehabilitation with ceramic veneers were included in the study. The data collection instrument consisted of a Google questionnaire, semi-structured, especially designed for the research, consisting of 1 subjective question and 15 objective questions about the indications, techniques, materials and care related to this treatment. Data were tabulated and descriptive analysis was performed. Results: 40 dentists from different regions of Brazil answered the questionnaire, 01 of which did not accept the TCLE and 39 had their responses validated. Conclusion: Professionals who work with ceramic laminates use different techniques and materials, most of which seek conservative approaches and follow the current literature. Light-curing cement is more widely used than dual cement. Constant updating is essential to offer better care to patients, remain competitive in the market and comply with the ethical and legal obligations of the profession.